About Quality of Optical Channels in Wavelength Division Multiplexing Systems of Optic Fibers - Mirazimova Gulnora Hasanovna (Universitas Ahmad Dahlan, 2018)
Researches and the analysis of factors of the systems influencing quality with division according to radiation wavelength are given in article. Especially the communication quality in systems with wave division of channels is influenced by hindrances from Four Wave Mixing. In this regard the technique of definition of number of products of nonlinear effect of Four Wave Mixing getting to ranges of working channels, results of calculation of combinational products for the different number of channels in systems with division according to radiation wavelength is given. Power of a hindrance of Four Wave Mixing in systems with wave division of channels is calculated. Methods of reduction of influences of these nonlinear effects are considered. Conclusions and recommendations on ensuring quality of optical channels are provided in systems with wave division.